(Phaseolus Vulgaris) by Replacing Soybean Meal on Egg Fertility and Qualities of Chicks of White Leghorn Hens. (Global Journal of Medical Research, 2015)
The study was to evaluate feeding processed kidney bean meal (PKBM) instead of soybean meal (SBM) on fertility, hatchability, embryonic mortality and chick quality of white leghorn (WL) hens. Replacement of SBM with PKBM in the diet did not affect the fertility, hatchability and embryonic mortality. Chick length (15.63, 15.00, 15.33, 15.03 and 14.33 (SEM =±0.02)) and chick weight (34.13, 34.20, 33.13, 33.06 and 32.47(SEM=±1.39)) for T1, T2, T3, T4 and T5 respectively, were significantly (P
Keywords: embryonic mortality; fertility; hatchability; kidney bean; soybean meal